Heart-brain interactions: clinical evidence and mechanisms based on critical care medicine - Qi, Chuyao; Wang, Wenting; Liu, Yanfei; Hua, Tianfeng; Yang, Min; Liu, Yue (Frontiers in Cardiovascular Medicine, 2024)
In this review paper, we search the recent literature regarding the application of the heart-brain interaction theories in the field of intensive care unit. Simultaneously, we methodically summarize the clinical evidence supporting its application in intensive care unit treatment, based on clinical randomized trials and clinical case studies. We delve into how it's applied in treating severely ill patients and in researching animal models for cardio-cerebral comorbidities, aiming to supply benchmarks for subsequent clinical trials and studies on mechanisms.